C2 Networks: The Invisible Threat in Your Infrastructure - Guram Donadze,; Viktor Zakaraia, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
C2 networks are a really important threat that often gets missed in today's companies. Attackers can use them to stick around, steal data, and plan other bad stuff without anyone noticing. This paper looks closely at C2 setups, how they've changed from simple central systems to trickier hidden channels that use encryption, DNS tunneling, and regular cloud services. We check out popular C2 tools like Cobalt Strike, Empire, Sliver, and Mythic, explaining how they work and avoid detection. We also explore ways to spot them, comparing old-school signature-based methods with newer anomaly-based and machine learning ways to find sneaky C2 communication. To back up what we talk about, we built a lab to copy real-world C2 situations, capturing and studying network traffic to find things that help in detection. The findings show that normal intrusion detection systems aren't great at catching encrypted C2 channels, which stresses using advanced behavioral and AI ways to detect them. This research helps to understand C2 network threats better and gives useful tips for cybersecurity folks to improve company defenses against these hidden but common threats.